Rekonstruksi Makna Jihad sebagai Paradigma Transformasi Sosial: Kajian Tafsir terhadap QS. Al-Hajj Ayat 78 - Catur Sri Lestari; Yeti Dahliana (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2026)
This study aims to reconstruct the understanding of jihad as a paradigm for social transformation and explain its relevance in the context of contemporary society. This understanding stems from the context of the time of the Prophet Muhammad (peace be upon him), where the call for jihad was always associated with conflict against infidels, namely, war. In its proper sense, the word jihad refers to a sincere desire to uphold the religion of Allah by exerting one's abilities. Jihad can be interpreted as an effort to strengthen the economy, improve the quality of education, and empower society socially. This study used library research and a qualitative method with a maudhu'i interpretation approach, analyzing Surah Al-Hajj, verse 78. The results show that the meaning of jihad in Surah Al-Hajj, verse 78, is not limited to warfare, but encompasses all forms of sincerity in carrying out Allah's commands, including spiritual, intellectual, social, and physical aspects. The research results show that the reconstruction of the meaning of jihad positions it as a paradigm of social transformation, namely as an active effort to create change towards a more just, peaceful, and civilized society. In the contemporary context, the concept of jihad has significant relevance in addressing various social problems, such as poverty, injustice, and moral crisis. Jihad can be realized in the form of social empowerment, improving the quality of education, moral improvement, and wise and persuasive preaching. Thus, jihad is no longer understood as a symbol of violence, but rather as a spirit of constructive struggle in building a better life.